2006
DOI: 10.1046/j.1360-0443.1995.9045458.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk-taking behaviour among injecting drug users currently, previously and never enrolled in methadone treatment

Abstract: This study compares the injecting and sexual risk-taking behaviour among injecting drug users (IDUs) currently, previously and never enrolled in methadone maintenance treatment (MMT). All subjects had injected during the 6 months prior to the day of interview. The current MMT group showed significantly lower injecting risk-taking behaviour subscale scores on the HIV Risk-taking Behaviour Scale (HRBS) of the Opiate Treatment Index than the previous MMT and non-MMT groups together. The current MMT group differed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Those who might benefit from opiate replacement therapy (ORT) most often do not receive appropriate care (Nunn et al, 2009). As a result, many return to opioid use after their release (Baker, Kochan, Dixon, Wodak, & Heather, 1995; Binswanger et al, 2007) and are at increased risk for infectious disease(Hammett, 2006; Inciardi & Needle, 1998), overdose (Binswanger et al, 2007) and reincarceration (Binswanger et al, 2007; Gore, Bird, & Ross, 1995; Lipton, Falkin, & Wexler, 1992). Provision of ORT during incarceration or linkage to ORT immediately post release is rare in correctional facilities currently (Nunn et al, 2009; Rich et al, 2005), despite evidence that ORT is effective in reducing morbidity and mortality associated with opiate dependence (Fiellin, Rosenheck, & Kosten, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Those who might benefit from opiate replacement therapy (ORT) most often do not receive appropriate care (Nunn et al, 2009). As a result, many return to opioid use after their release (Baker, Kochan, Dixon, Wodak, & Heather, 1995; Binswanger et al, 2007) and are at increased risk for infectious disease(Hammett, 2006; Inciardi & Needle, 1998), overdose (Binswanger et al, 2007) and reincarceration (Binswanger et al, 2007; Gore, Bird, & Ross, 1995; Lipton, Falkin, & Wexler, 1992). Provision of ORT during incarceration or linkage to ORT immediately post release is rare in correctional facilities currently (Nunn et al, 2009; Rich et al, 2005), despite evidence that ORT is effective in reducing morbidity and mortality associated with opiate dependence (Fiellin, Rosenheck, & Kosten, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…MMT is an effective intervention for the management of heroin addiction, reducing levels of heroin use and of risky behaviors (injecting and needle sharing).Therefore, MMT reduces the risk of HIV infection among opiate-dependent patients [9], [10]. But the effectiveness of MMT to control the spread of HCV infection among IDUs has been disputed [11], [12].Despite the widespread use of MMT for opioid addiction in China, there are still many addicts who have never enrolled in MMT [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the fourth study 4 there was a nonsignificant reduction in the mean score between intake and 6-month follow-up. Another study 23 reported significantly lower drug risk scores for a cohort of IDU in methadone maintenance with cohorts not in treatment at the time of assessment.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…A third study 4 reported a nonstatistically significant reduction. One study 23 found no difference in sex-related risk scores for IDU currently in methadone maintenance treatment, compared with those previously in, or with no prior history of methadone maintenance.…”
Section: Effect Of Methadone Treatment On Sex-related Riskmentioning
confidence: 99%